Создание CAPS-маркера к гену FAD3B, контролирующему синтез α-линоленовой кислоты у льна (Linum usitatissimum L.) - Лемеш, В.А.; Богданова, М.В. (Фактори експериментальної еволюції організмів, 2015)
The aims of this study was to develop CAPS marker to the fad3B gene controlling the synthesis of α-linolenic acid in linseed (Linum usitatissimum L.). Methods. DNA sequencing was perfomed on an automatic ABI 3500 Genetic Analyzer (Applied Biosystems). For the sequencing analysis and primers’ design we used the Vector NTI Advance ® Software 11.5.0 (©Invitrogen, США). Results. We developed the codominant CAPS marker MutFad3 allowing to detect the mutant allele of the flax fad3B gene responsible for reduced α-linolenic acid levels in linseed oil. After amplification of 600 bp product using the MutFad3 primer set, products were digested with BalI generating two fragments (385 and 215 bp) in high-linolenic genotypes with the wild-type fad3B gene. In contrast, all low-linolenic genotypes with the mutated fad3B genes showed only 600 bp band after BalI treatment. The heterozygous genotypes with intermediate levels of α-linolenic acid showed three fragments – 215, 385 and 600 bp. Conclusions. Using these codominant markers, it was possible to classify plants as homozygous mutant, homozygous wild type, or heterozygous at fad3 loci, that can be used to breed new flax varieties of food or industrial quality.